2010
DOI: 10.1089/gtmb.2009.0153
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Phenylalanine Hydroxylase Gene in Iranian Azeri Turkish Patients with Phenylketonuria

Abstract: These intriguing preliminary findings confirm IVS10-11G>A as a major mutation among Mediterranean mutations. For this population, exons 7 and 11 and adjacent introns, which carry more than 75% of the mutations, would have to be primarily screened. However, the other exons must be studied when either one or no mutations are found in the primary screening. The mutation spectrum in the patients with Azeri Turkish ethnic origin differed from that observed in patients from other Mediterranean countries and further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
(9 reference statements)
5
15
0
Order By: Relevance
“…This was also found to be true in our cohort, although other notable types of mutations were detected. The c.1066-11G > A splicing mutation was the most common mutation in this cohort, consistent with the high prevalence reported in several other populations, including in Iran (Bonyadi et al 2010;Zare-Karizi et al 2011;Hamzehloei et al 2012;Ajami et al 2013). The prevalence of certain other mutations in this cohort was considerably different from the prevalence reported in previous studies and in other populations.…”
Section: Mutation Detection and Landscape Of Pah Mutations In This Cosupporting
confidence: 80%
“…This was also found to be true in our cohort, although other notable types of mutations were detected. The c.1066-11G > A splicing mutation was the most common mutation in this cohort, consistent with the high prevalence reported in several other populations, including in Iran (Bonyadi et al 2010;Zare-Karizi et al 2011;Hamzehloei et al 2012;Ajami et al 2013). The prevalence of certain other mutations in this cohort was considerably different from the prevalence reported in previous studies and in other populations.…”
Section: Mutation Detection and Landscape Of Pah Mutations In This Cosupporting
confidence: 80%
“…Organism/amino acid residue 372 373 374 375 376 377 378 To date, more than 30 different mutations have been detected in patients with PKU living in Iran (Bonyadi et al, 2010;Zare-Karizi et al, 2011). This study is the first to report five other mutations, Y356X, S231P, I224T, IVS11-2A>G, and V388M, in an Iranian population.…”
Section: Discussionmentioning
confidence: 79%
“…This mutation has been identified as the most common mutation in Mediterranean populations such as Turkey (Dobrowolski et al, 2011), Italy (Daniele et al, N. Ajami et al 2007), Spain (Desviat et al, 1999), Egypt (Effat et al, 1999), and Israel (Bercovich et al, 2008). In previous studies that have been performed in Iran, IVS10-11G>A was also identified with the highest frequency (Bonyadi et al, 2010;Zare-Karizi et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…R261X, the most common mutation in our study, is also detected in Iran[1011] and some countries such as Croatia,[2] Italy,[13] Brazil,[14] Germany,[2] Korea,[15] Lithuania[16] and Portugal[17] [Table 5]. This mutation as well as R176X and R243X are nonsense mutations that lead to a premature step in translation.…”
Section: Discussionmentioning
confidence: 59%
“…The frequencies of these mutations in Iranian population is <2%. [11] Furthermore, there is no report of detection of these two mutations in Isfahan[9] and Azeri Turkish (northwestern of Iran)[10] populations [Table 5]. …”
Section: Discussionmentioning
confidence: 99%